RT‐CGM in conjunction with CSII vs MDI in optimizing glycaemic control in T1DM: Systemic review and meta‐analysis. Issue 2 (4th February 2022) - William, Jimmy; McCluskey, Jane; Gleeson, Nigel
Abstract: Introduction: To determine the impact of real‐time continuous glucose monitoring (RT‐CGM) in conjunction with 'Open loop'‐ continuous subcutaneous insulin infusion (CSII) as compared to conventional multiple daily injections (MDI) in type 1 diabetes. Methods: We explored the COCHRANE database, MEDLINE, WEB OF SCIENCE, GOOGLE SCHOLARS, PUBMED, EMBASE, and cited literature in articles retrieved (2010–2021) for all randomized controlled trials and real‐world trials of more than 6 months duration in patients with type 1 diabetes that compared RT‐CGM+CSII vs RT‐ CGM+MDI. A total of 1645 publications have been identified; however, only 3 trials fulfilled our inclusion criteria with a total number of 150 patients (72 patients using RT‐CGM+CSII and 78 patients on RT‐CGM+MDI). A Systematic Review and Meta‐analysis were carried out. Results: No statistically significant reduction in HbA1c was found on comparing RT‐CGM+CSII vs RT‐ CGM + MDI, with p ‐value = .75. Likewise, impact on TIR, weight and insulin usage was found to be statistically insignificant with p ‐value of 0.15, 0.75 and 0.20 respectively. There was an overall homogeneity between the 3 trials in respect to all previous variables with I 2 being 0%. Conclusions: Real‐time continuous glucose monitors in conjunction with MDI open‐loop CSII had a similar impact on HbA1c, weight, insulin usage and TIR. In addition, RT‐CGM when combined with CSII was associated with higher costs and reduced quality of life, hence RT‐ CGM+MDI can be considered as a cheaper, safer yet equivalent substitute. Review Registration: This study was registered in PROSPERO (International prospective register of systematic reviews). Registration Name: RT‐CGM in conjunction with CSII vs MDI in optimizing glycaemic control in T1DM: a systematic review. Registration No: CRD42021255333. Accessible at: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021255333 . Amendments: Few amendments to the above‐mentioned registration were made: (1) Title (Meta‐analysis was added). (2) Prof. Gleeson was added as an author. (3) Real‐world trials were included. (4) Outcomes required in studies as per our inclusion criteria amended to include at least 1 outcome. (5) Bias risk was assessed by the CASP tool. Abstract : This is the first systematic review and meta‐analysis comparing RT‐CGM+CSII vs RT‐CGM+MDI and its impact on glycaemic control. It is a recap of the last 22 years' novel interventions in the field of diabetes. The chief result of our meta‐analysis is that RT‐CGM in conjunction with CSII or MDI has a similar impact on the glycaemic outcome, weight, insulin usage and TIR.